REPOSISI BMT SEBAGAI LEMBAGA KEUANGAN SYARIAH PRO RAKYAT - Saripudin (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2014)
Syariah economic development especially in the field of financial institutions and banks so rapidly. This can be seen from the development of the number of Syariah Banks and Syariah banking turnover increasing from year to year . But the development of Syariah Banks are still not even maybe not at all perceived by the poor. They still do not have access to banking industry. This writing try elaborating on a model of Syariah Financial Institutions that can be more pro people by trying to do compare between Syariah Bank and BMT (Financial Institution non Bank). From the comparation known that more BMT become allows Syariah Financial Institutions for the poor (pro the people) because as financial institutions non bank, BMT not bound with Bank Indonesia Regulations.